Quantum Dot Lasers: Directly Modulated Single‐Mode Tunable Quantum Dot Lasers at 1.3 µm (Laser Photonics Rev. 14(3)/2020). Issue 3 (12th March 2020) - Wan, Yating; Zhang, Sen; Norman, Justin C.; Kennedy, MJ; He, William; Tong, Yeyu; Shang, Chen; He, Jian‐Jun; Tsang, Hon Ki; Gossard, Arthur C.; Bowers, John E.
Abstract : In article number 1900348, Yating Wan and co‐workers demonstrate directly modulated, single‐mode, tunable InAs/GaAs quantum dot (QD) lasers at 1.3 µm wavelength range, by combining the advantages of QDs with a special designed half‐wave coupled cavity structure. Without involving re‐growth steps or sub‐wavelength grating lithography, 27‐channel wavelength switching was achieved with side‐mode‐suppression‐ratio of around 35 dB and output power of over 9 mW.